Enantioselective binding of additives to chiral crystals - Carter, D.; Kahr, B.; Rohl, Andrew (AMER CHEMICAL SOC, 2012)
The autocatalytic Soai reaction gives abundant evidence of the enantioselective adsorption of organic compounds on a variety of crystals. Computational modelling can provide insight into mechanisms of enantioselectivity, thus our aim has been to develop a robust computational methodology that can be applied to understanding crystal-biased asymmetric synthesis. Using a combination of forcefield-based calculations coupled with simulated annealing calculations, we have examined two model crystal systems - g-glycine and N-(2-thienylcarbonyl)glycine. The simulations provide binding energies of Soai reactant and product molecules on the exposed faces of the catalytic crystals. Using these energies, a Boltzmann distribution can predict the most abundant orientations of these molecules at each surface, and information regarding the final product can be derived. In the case of N-(2-thienylcarbonyl)glycine, this can be correlated with stereochemical outcomes of the Soai reaction and the absolute structure of the crystals determined by the anomalous dispersion of X-rays and circular dichroism spectroscopy.